Evaluación de la accesibilidad del transporte público en la parroquia Buenavista - Sarango Barreto, Nelly Paulina (Machala : Universidad Técnica de Machala, 2024)
This study focused on the evaluation of public transportation accessibility in the Buenavista parish, Pasaje canton, El Oro province, with the aim of determining the accessibility index using indicators such as service frequency, waiting time, walking time and distance, and the location of bus stops. The locations evaluated were each of the formal bus stops in the parish. To carry out the research, a mixed research approach was adopted, combining both quantitative and qualitative methods. The quantitative part focused on variables such as service frequency, waiting time, and distance traveled, while the qualitative part explored the population's perceptions regarding accessibility and bus stops. A documentary methodology was used to gather background information on transportation in the parish, and a field methodology was applied through surveys of residents and observation sheets. Two methods were used to measure accessibility: PTAL (Public Transport Accessibility Level) and the Zapata method. According to PTAL, the parish has a low index of 2.02, indicating poor accessibility, with stop 4 being the least accessible (1.75) and stop 2 the most accessible (2.31), although still insufficient. In contrast, the Zapata method revealed an average of 20.50 minutes, with stop 2 being the most accessible (17.50 minutes) and stop 4 the least accessible (23.75 minutes). Although the index from the Zapata method is relatively better, both methods show that public transportation accessibility in the parish remains limited and requires improvements for a more efficient and accessible service.
El presente trabajo se enfocó en la evaluación de la accesibilidad del transporte público en la parroquia Buenavista, cantón Pasaje, provincia de El Oro, con el propósito de determinar el índice de accesibilidad mediante indicadores como frecuencia del servicio, tiempo de espera, tiempo y distancia de caminata y ubicación de las paradas. Los lugares evaluados fueron cada una de las paradas formales que existen en la parroquia. Para llevar a cabo la investigación, se adoptó un enfoque de investigación mixto, combinando métodos cuantitativos y cualitativos. La parte cuantitativa se enfocó en variables como la frecuencia del servicio, tiempo de espera y distancia recorrida, mientras que la cualitativa exploró las percepciones de la población sobre la accesibilidad y las paradas. Se utilizó una metodología documental para obtener antecedentes sobre el transporte en la parroquia y una metodología de campo a través de encuestas a los habitantes y fichas de observación. Se emplearon dos métodos para medir la accesibilidad, el PTAL (Nivel de Accesibilidad al Transporte Público) y el método de Zapata. Según el PTAL, la parroquia tiene un índice bajo de 2.02, indicando una accesibilidad deficiente, con la parada 4 como la menos accesible (1.75) y la parada 2 la más accesible (2.31), aunque aún insuficiente. En contraste, el método de Zapata reveló un promedio de 20.50 minutos, con la parada 2 más accesible (17.50 minutos) y la parada 4 la menos accesible (23.75 minutos). Aunque el índice del método de Zapata es relativamente mejor, ambos métodos muestran que la accesibilidad al transporte público en la parroquia sigue siendo limitada y requiere mejoras para un servicio más eficiente y accesible.
Keywords: EVALUACION; MOVILIDAD; TRANSPORTE PUBLICO; ACCESIBILIDAD